Anti-fatigue effects of polysaccharides extracted from Rhodiolae Radix - Li, Fenglin; Xiao, Furen; Qi, Junsheng (International Current Pharmaceutical Journal, 2013)
The purpose of the present study was to determine the effects of polysaccharide from Rhodiolae Radix (PRR) on physical fatigue using a forced swimming test in male mice. 96 mice were divided randomly into four groups based on body weight (n = 24). One of the groups was the control group; the others were PRR supplemented groups (25, 50 and 100 mg/kg body weight). Forced swimming test of mice were carried out after 28 days of PRR administration, and the blood lactic acid (BLA), blood urea nitrogen (BUN), liver glycogen and muscle glycogen contents were determined. The data suggest that PRR can extend the exhaustive swimming time of the mice, as well as increase the tissue glycogen contents, and decrease the BLA and BUN contents. These results indicated that PRR had significant anti-fatigue effects. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13579 International Current Pharmaceutical Journal, February 2013, 2(3): 49-52